2018
DOI: 10.1055/s-0038-1668139
|View full text |Cite
|
Sign up to set email alerts
|

European Paediatric Surgeons' Association Survey on the Management of Pediatric Appendicitis

Abstract: Some aspects of appendicitis management lack consensus, particularly appendix mass and intraperitoneal abscess. Evidence-based guidelines should be developed, which may help standardize care and improve clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 61 publications
0
5
0
2
Order By: Relevance
“…Conflicting results have also been reported after laparoscopic appendectomy for complicated appendicitis [ 10 , 11 ]. In these patients, the type of drain tube and distance from the abdominal wound to the most distal end of the tube play a role in the outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Conflicting results have also been reported after laparoscopic appendectomy for complicated appendicitis [ 10 , 11 ]. In these patients, the type of drain tube and distance from the abdominal wound to the most distal end of the tube play a role in the outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…In 2018, in a wide-ranging study, Tom et al 19 found that of the 58511 appendectomies conducted in children’s hospitals in the USA between 2003 and 2012, 70% were done using laparoscopy, compared to 53% of the ∼1.2 million conducted at non-children’s hospitals. Zani et al 20 summarized the results of the European Pediatric Surgeons’ Association survey on the management of pediatric appendicitis, compiled from 169 respondents from 42 countries (24 European). For simple appendicitis, laparoscopy was the preferred method for 89%, while for perforated appendicitis, it remained the method of choice for 81%.…”
Section: Discussionmentioning
confidence: 99%
“…Тоді як у розвинутих країнах ЛА є стандартним методом лікування дітей з ГА [47,57,72], то у краї-нах, що розвиваються, цей метод лікування тільки набуває поширеності [3]. Це в першу чергу зумовлено тим, що значна частка пацієнтів госпіталізується з клінічною картиною ускладненого ГА, і хірурги не ризикують виконувати мініінвазивного втручання, а, крім того, зберігаються проблеми кривої навчання.…”
Section: результати дослідження та їх обговоренняunclassified
“…Незважаючи на недоведеність ефективності лаважа черевної порожнини, багато хірургів вважають за доцільне промивати черевну порожнину для «розведення» гнійного вмісту та «очищення» зони запалення, керуючись висловом «розведення є вирішенням проблеми забруднення -dilution is the solution to pollution» [16, 26,35]. За даними опитування Європейської асоціації дитячих хірургів, лише 29% хірургів завжди промивають черевну порожнину при ГА, 58%лише за наявності гнійного випоту, а 13% -переважно лаваж не використовують [72]. Серед наших пацієнтів лаваж проведений у 23,7% при ВА і у 32,9% при ЛА.…”
Section: результати дослідження та їх обговоренняunclassified